2007
DOI: 10.1021/la062875i
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Phase Behavior of DMPG:  The Exclusion of Continuous Network and Dense Aggregates

Abstract: 1,2-Dimyristoyl-sn-glycero-3-phospho-rac-glycerol has been suggested to form at intermediate temperatures and at high concentrations in low-salt solutions as a continuous sponge phase (Heimburg, T.; Biltonen, R. L. Biochemistry 1994, 33, 9477-9488). In the present study, the changes in signals seen for a range of fluorescent probes during phase transformations of this phospholipid indicate continuous melting and a change in lipid packing, in accordance with previous reports. However, in accordance with Lamy-Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 43 publications
5
54
1
14
Order By: Relevance
“…However, electron spin resonance (ESR) experiments demonstrated that the lipid monomers were not exchanged between vesicles, which did not support the existence of the sponge phase [11]. Other proposed model raised by SAXS data analysis suggests that new lamellar phase with pores or porous spherical vesicle is the most plausible structure [3,7,10,12,13]. Appearance of such intermediate structure during the chain-melting transition motivated us to characterize the phase behavior of DMPG systems by the use of a rheo-physical method, a *Current address: Division of Applied Physics, Graduate School of Engineering, Hokkaido University, N13W8, Sapporo 060-8628, Japan E-mail: sfujii@eng.hokudai.ac.jp combination of rheology and small angle X-ray scattering.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, electron spin resonance (ESR) experiments demonstrated that the lipid monomers were not exchanged between vesicles, which did not support the existence of the sponge phase [11]. Other proposed model raised by SAXS data analysis suggests that new lamellar phase with pores or porous spherical vesicle is the most plausible structure [3,7,10,12,13]. Appearance of such intermediate structure during the chain-melting transition motivated us to characterize the phase behavior of DMPG systems by the use of a rheo-physical method, a *Current address: Division of Applied Physics, Graduate School of Engineering, Hokkaido University, N13W8, Sapporo 060-8628, Japan E-mail: sfujii@eng.hokudai.ac.jp combination of rheology and small angle X-ray scattering.…”
Section: Introductionmentioning
confidence: 94%
“…In any case, conformation change of a head group and acyl chain in DMPG monomer due to the chain-melting transition would play a role on variable morphology [6,8,15,16]. Complex endotherm profiles with multi-peaks in the same DMPG system indicate that the chain-melting continuously proceeds, and thus a chain packing in the membrane also changes continuously [2,7]. In the intermediate phase, therefore, coexistence of the fluid membrane with high curvature and rigid domains would be expected [6].…”
Section: Rheometrymentioning
confidence: 99%
See 3 more Smart Citations